DESAIN DAN IMPLEMENTASI APLIKASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR BERBASIS WEB - Kurniawan, Kurniawan; Sahfitri, Vivi ; Bakti, A. Mutatkin (JURNAL ILMIAH MATRIK, 2017)
Archiving activity the correspondence is one of the important things that must be considered in the administrative activities in Higher Education. A lot of the stakeholders raises the number of incoming and outgoing letters associated with academic activities. A number of letters made and received administrative section of the University of Bina Darma resulted in archiving done so far by manually recording that it felt less effective and efficient again. This research aims to design and build the application of incoming and outgoing letter archiving that can be used to assist and improve performance in the administrative. Research activities will be conducted gradually starting from data collection activities to produce applications. The results of this research is the application archiving of incoming and outgoing letter as a tool in improving the efficiency, accuracy and security of archived documents and can more easily do archiving incoming mail and outgoing mail and archive search of incoming and outgoing letter. Keywords: Letter, Administrative, Correspondence, Efficiency, Accuracy